Development of Novel 3d Printable Graphene-based Composite Towards Fabrication of Thin Film Electrode Material - Le T. M., Hanh; Do, T. Thuy; Hoang, T. Dung; Doan, T. Tung; Vu, X. Minh; Pham, T. Lan; Le, T. Lu; Tran, D. Lam; Nguyen, T. Dung (Communications in Physics, 2020)
Graphene/polymer composite thin film electrodes have many important applications, but the fabrication of these electrodes is often difficult because of poor processability of graphene. This paper presents the primary results on using 3D printing technique for thin film electrode preparation from graphene-based composite ink. The printing ink was synthesized from graphene oxide (GO), polyvinyl alcohol (PVA) as a binder and stabilizer, and ascorbic acid (AA) as a reducing agent. The measured zeta potential value showed that PVA can make GO ink more stable, the absolute value of zeta potential increased from 10.1 mV (without PVA) to 31.4 mV (with 12 wt. % PVA). The thin film electrodes can be easily printed using GO/PVA/AA composite ink, and obtained voltammograms recorded on the surface of these electrodes in 5 mM K3[Fe(CN)6]/K4[Fe(CN)6] solution clearly indicated the GO reduction by AA. The best electrochemical properties of printed electrodes were founded in the case of composite ink with wt/wt ratio GO:PVA:AA = 80:12:8. The cyclic voltammetric results demonstrated the linear dependence of the anodic and cathodic signals of redox couple [Fe(CN)6]4-/K3[Fe(CN)6]3- with the square root of scan rate, indicating a reversible redox reaction on the electrode surface. The thin films printed from GO/PVA/AA composite ink can be used as electrode material for diverse applications in electrochemistry.